RANCANGAN SISTEM PRESENSI MAHASISWA MENGGUNAKAN QR CODE DENGAN FITUR GEOLOCATION DAN ENKRIPSI AES - Alfan Rosid, Mochamad; Sumarno, Sumarno (Jurnal Informatika, 2021)
This research aims to create a student presence system using the QR Code (Quick Response Code) with AES encryption, when the learning process will begin, lecturers display QR Code for further scans by students through their smartphones that have been installed academic information system, data presences will be automatically stored in the database, the data can be known directly by lecturers and students. Data security uses AES encryption methods and in order to ensure that students are actually present then this research also implements Geolocation, if Geolocation on the student's smartphone is not the same as that in the presences system then the student is not able to perform the presences. From the results of the research, the system can run well, with the existence of this system can simplify the process of presences and increase efficiency because no more presences printed on paper.